Mobility Dynamics and Knowledge Work: The Change of Job-Related Circular Mobility - Strambach, Simone; Kohl, Hendrik (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
An increasing importance of mobile and com- plex forms of working and living has been noticed in re- cent mobility research. These developments are closely linked to the socio-economic structural change toward a knowledge economy and to changes in the organization of employment. So far only few empirical results indicate that knowledge workers are more mobile than other em- ployees. However, the relationship between knowledge-in- tensive activities and job-related—especially the so-called circular—mobility has not been systematically examined in-depth. Merging interdisciplinary mobility research with the spatial innovation and knowledge science seems to be a promising approach for utilizing synergy potentials that allow a more differentiated analysis of the fluid, spatiotem- poral connection between knowledge work and its complex implications for the job-related circular mobility.
Keywords: Knowledge economy; Knowledge work; Job-related mobility; Time-space dynamic